THE USE OF METAPHORS IN LITERARY TEXTS IN ENGLISH AND UZBEK - Nargiza Suyarova; Jasmina Ismatova (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Metaphor is a fundamental stylistic device in literature that enriches language, conveys abstract concepts, and evokes emotional responses. This study explores the use of metaphors in literary texts in English and Uzbek, highlighting both universal and culture-specific features. The paper examines how metaphorical expressions reflect cultural values, worldview, and cognitive patterns in each language. Comparative analysis reveals similarities in metaphorical mechanisms while emphasizing the influence of cultural context on metaphorical choices. The findings contribute to a deeper understanding of cross-cultural literary analysis and translation studies.